(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
An interaction of palladium (II) anionic complex with dye of acridine row rivanol has been studied. Formed compound could be extracted by iso-amylacetate. Maximal extinction for dye aqueous solutions and for extracts of compound and “blind” extracts as well is observed at the same value of wavelength is 365 nm. Under optimal acidity conditions (pH 2 by sulphuric acid) palladium (II) is extracted practically quantitatively (R = 88.5%) during 1 min shaking. The optimal quantities of potassium iodide and dye are correspondingly 0.6 mL of 1·10–2 mol/L and 0.6 mL of 0.05% solutions. The iso-amylacetic extracts of coloured ionic associate are submitted to the main low of spectrophotometry in the 0.3–3.8 mcg/mL range of palladium (II) contents. Effective coefficient of molar extinction equals to 1.8·10–4 cm–1. The molar ratio between palladium (II) iodide complex and rivanol in forming compound has been determined, which is 1:1. The influence of interfering and accompanying elements on the determination of palladium using rivanol has been studied. Extraction-absorbtiometric methods elaborated have been applied for determination of palladium in various samples of catalysts of organic synthesis.